352 Improving Consent for Elective Inguinal Hernia Repair. (28th February 2022) - Lorimer, J.
Abstract: Introduction: Litigation costs the NHS billions each year. To avoid litigation against known risks of elective surgery it is important that proper consent it obtained. The initial aim was to establish the percentage of patients consented fully for inguinal hernia repair at Warrington and Halton teaching hospitals, a moderately sized district general hospital. The Trust uses the information produced by EDIO as their standard of informed consent. One of the main outcomes was the rate of consent for risk of chronic pain as this is the 3 rd most commonly litigated complication and an identified risk of inguinal hernia repair. Method: A retrospective audit looking at consent forms for adult men who underwent elective open inguinal hernia repair, over a 6-month period in 2019, was undertaken. After the first audit the results were discussed at the local audit meeting and teaching was given for what should be included on a consent form for inguinal hernia repair. A second cycle of the audit was run in 2021, after the COVID pandemic, to assess if consenting had improved. Results: 66 vs 22 cases met the inclusion criteria for the first and second 6-month periods respectively. An improvement in consent for chronic pain was observed with 91% of patients in the second cycle being consented for chronic pain vs 79% in the first cycle. In the second cycle 32% of patients were also consented for the risk of "COVID". Conclusions: Teaching proper consent works effectively to improve consenting.